Hypothalamic Vasopressin-Producing Tumors: Often Inappropriate Diuresis But Occasionally Cushing Disease. (February 2019) - Asa, Sylvia L.; Ezzat, Shereen; Kelly, Daniel F.; Cohan, Pejman; Takasumi, Yuki; Barkhoudarian, Garni; Heaney, Anthony P.; Ridout, Rowena; Chik, Constance L.; Thompson, Lester D.R.; Gentili, Fred; Mete, Ozgur
Abstract : Tumors of hypothalamic neurons that produce vasopressin are rare. We retrieved all cases of vasopressin-positive tumors in the sellar region from the database of the Department of Pathology. Five cases fulfilled the selection criteria, representing the first series of such tumors. Clinical, radiologic, and pathologic features were reviewed. Four tumors classified as neurocytomas were identified in 3 females and 1 male patient; the ages at onset of symptoms ranged from 17 to 40 years. All were large sellar masses with suprasellar extension and/or invasion of the parasellar sinuses. Three patients had the syndrome of inappropriate antidiuresis; in one of these, a 6-year history was initially considered to be idiopathic. One patient died of progressive disease; 3 had incomplete resections and are being followed. In contrast to these patients with neurocytoma, a 65-year-old woman had Cushing disease and a 0.8 cm mass that was completely resected at transsphenoidal surgery; this tumor was a gangliocytoma producing vasopressin associated with corticotroph hyperplasia. We postulate that the small amount of vasopressin secreted by this mature gangliocytic tumor was locally bound to corticotrophs, resulting in hyperplasia and Cushing disease, without sufficient overproduction to cause systemic effects of vasopressin excess. Hypothalamic neurocytoma is a tumor that can mimic pituitary neuroendocrine tumors and olfactory neuroblastoma but is distinguished by positivity for neurofilaments, NeuN, and TTF-1 and negative staining for adenohypophysial biomarkers. Our cases illustrate that neurocytoma and gangliocytoma are 2 variants of tumors of hypothalamic neurons that can produce vasopressin. The morphologic and proliferative features of these 2 tumor types represent 2 ends of a spectrum; their function also can result in divergent clinical manifestations, one characterized by reduced urine output and the other by the more insidious features of glucocorticoid excess.